2017
DOI: 10.18203/issn.2455-4529.intjresdermatol20170794
|View full text |Cite
|
Sign up to set email alerts
|

A study on histopathological changes in lesions of vitiligo in Karnataka population

Abstract: <p class="abstract"><strong>Background:</strong> <span lang="EN-IN">Vitiligo is considered to be symptom less and its presentation is boundless varying from isolated focal lesion to bizarre generalized lesions. The present study was undertaken to study the histopathological changes in lesions of vitiligo in south Indian population.</span></p><p class="abstract"><strong>Methods:</strong> 150 patients with mild to moderate vitiligo features attending the outp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…In current study, on histopathology, hyperkeratosis of epidermis was observed in 52% which was found significant statistically(p=0.018) concordant to the study done by Verma et al (63.3%) but discordant with Nagaral GV et al (13.3%), similarly lymphocytic infiltration was 86% in our study which was similar to Sharquie KE et al (80%) but different from Nagaral et al (37.7%). [17][18][19] Also absence of melanocytes was 78% in our study which was also significant statistically (p=0.048) compared to 52% in Nagaral et al and presence of melanocytes (mild) was 44% in contrast to 13.3% of Nagaral et al 19 Dermoscopy is a non-invasive technique helping the doctor diagnoses vitiligo at an early stage and to label it as stable or unstable. In our study we found various findings which were both concordant and discordant with several studies (Table 2).…”
Section: Discussionmentioning
confidence: 49%
“…In current study, on histopathology, hyperkeratosis of epidermis was observed in 52% which was found significant statistically(p=0.018) concordant to the study done by Verma et al (63.3%) but discordant with Nagaral GV et al (13.3%), similarly lymphocytic infiltration was 86% in our study which was similar to Sharquie KE et al (80%) but different from Nagaral et al (37.7%). [17][18][19] Also absence of melanocytes was 78% in our study which was also significant statistically (p=0.048) compared to 52% in Nagaral et al and presence of melanocytes (mild) was 44% in contrast to 13.3% of Nagaral et al 19 Dermoscopy is a non-invasive technique helping the doctor diagnoses vitiligo at an early stage and to label it as stable or unstable. In our study we found various findings which were both concordant and discordant with several studies (Table 2).…”
Section: Discussionmentioning
confidence: 49%
“…In our study, Perivascular inflammation was among majority (71.2%) of patients. According to Nagaral and Karibasappa (2017) 31 observed dermis with mild perivascular lymphocytic infiltration and acanthosis along with mono nuclear cell infiltration in the upper dermis.Similar to our study, Alikhan A et al(2011) 2 reported perivascular inflammatory infiltrate in 30% of cases in a review of 74 vitiligo specimens. In our study, Lichenoid inflammation was among more than one third of patients (19.2%).Attili and Attili (2013) 32 found that focal lichenoid inflammation of varying degrees around epidermal/adnexal melanocytes was identified as a common feature in evolving lesions of both SV (segmental vitiligo) (78%) and GV (Generalised vitiligo) (70%).…”
Section: Discussionmentioning
confidence: 98%
“…From each block, several 5 micron (5 µm) thick sections were taken and stained with hematoxylin and eosin (H&E) stain for the routine histopathologic evaluation. 16 Sections on positive charged slides were immune histochemical (IHC) stained of ATG7. Assessment of ATG7 IHC stained slides in both epithelium and stroma (as staining state: either positive or negative, staining localization.…”
Section: Skin Biopsiesmentioning
confidence: 99%